Trendy upadłości przedsiębiorstw w Polsce - Gołębiowski, Grzegorz (The Trends for Insolvency of Companies in Poland, 2006)
The problems connected with insolvency of business enterprises become more and more often an issue of academic research. It appears that among others there is a correlation between an economic cycle and the number of insolvency of business enterprises. This correlation is especially strong in Poland. Moreover, in the article there are analyzed tendencies for insolvency of companies in Poland taking various measurements and criteria into account. In a few cases there are considered indicators observed in other countries in Europe and all over the world
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 240-246